Propranolol in a case series of 174 patients with complicated infantile haemangioma: indications, safety and future directions. (25th March 2013) - Hermans, D.J.J.; Bauland, C.G.; Zweegers, J.; van Beynum, I.M.; van der Vleuten, C.J.M.
<x xml:space="preserve">Abstract</x> Summary Background Infantile haemangioma (IH) is a benign, common and self‐limiting tumour of infancy; only a minority of cases need active treatment. Currently, propranolol appears superior to classic treatments. Objectives To document in a prospective study indications and side‐effects of propranolol for complicated IH in a large patient group. Methods Analysis of prospectively collected data was performed on 174 patients with IH treated with propranolol in a tertiary referral centre from September 2008 to January 2012. Results The group consisted of children with a potentially threatening and/or complicated IH; the girl/boy ratio was 123/51, and the mean age at the start of treatment was 4·8 months. In 173 cases (99·4%), treatment was successful, as assessed nonquantitatively by clinical observation. This striking effect was characterized by immediate cessation of growth, softening, fading of the erythema and rapid induction of regression. The mean duration of treatment was 10·7 months. The most important adverse effects were hypotension (3·4%), wheezing (9·2%), nocturnal restlessness (22·4%) and cold extremities (36·2%). In one patient, propranolol was stopped. In 15 patients it was necessary to reduce the dose, although the lower dose was still effective. Conclusions In this study, propranolol was effective and safe in almost all patients with complex IH. Administration of systemic medication to an infant with a benign condition requires careful consideration, as only a minority of patients with IH require an active medical intervention. A shift of the indication of propranolol for IH is evident, expanding its application for life‐threatening situations or severe functional impairment to early prevention of disfigurement or cosmetically permanent sequelae. However, the indication for such an active approach should be determined by experienced physicians.